Correction: Social robots in research on social and cognitive development in infants and toddlers: A scoping review. - Solveig Flatebø; Vi Ngoc-Nha Tran; Catharina Elisabeth Arfwedson Wang; Lars Ailo Bong (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0303704.].